THEORETICAL BASIS AND PRACTICAL EXPERIENCES OF TAX SHIFTING WITH REFERENCE TO AGRICULTURE - Milošević, Goran; Kulić, Mirko (Economics of Agriculture, 2011)
Country, starting from the general interests, establishes the financial distribution of burden, but individuals burdened by taxes, having their own personal interests, do not accept this distribution. Taxpayer must pay the taxes, but he reacts in that way that he transfers the tax burden to other persons. Tax shifting should be understood as economic process caused by a tax procedure by which the direct financial burden is being transferred, through price adjustment, from a taxpayer to one or several other persons. Tax shifting exists when a person – taxpayer is different from a person that actually bears the tax burden. Tax shifting also appears in agriculture. This line of activity, due to its specificity, specificity of natural conditions and the very nature of activity, undergoes a special tax treatment, but is also specific in the sphere of tax shifting.